2011
DOI: 10.1007/s10863-011-9366-3
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Diiodo-L-Thyronine increases FoF1-ATP synthase activity and cardiolipin level in liver mitochondria of hypothyroid rats

Abstract: Short-term effects of 3,5-L-diiodothyronine (T(2)) administration to hypothyroid rats on F(o)F(1)-ATP synthase activity were investigated in liver mitochondria. One hour after T(2) injection, state 4 and state 3 respiration rates were noticeably stimulated in mitochondria subsequently isolated. F(o)F(1)-ATP synthase activity, which was reduced in mitochondria from hypothyroid rats as compared to mitochondria from euthyroid rats, was significantly increased by T(2) administration in both the ATP-synthesis and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
4
16
0
Order By: Relevance
“…A great body of evidence has reported that T2, previously considered only a T3 catabolite, is able to mimic some of T3’s effects on the metabolism [11]. T2 action appears to be more rapid than that of T3, and seems to be independent of protein synthesis [11,12,13,14,15]. It has been shown that T2 administration to rats increases their resting metabolic rate by modulating mitochondrial function [16,17,18], prevents diet-induced obesity by enhancing burning of fats [19], and reduces liver steatosis in rats fed on a high-fat diet [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great body of evidence has reported that T2, previously considered only a T3 catabolite, is able to mimic some of T3’s effects on the metabolism [11]. T2 action appears to be more rapid than that of T3, and seems to be independent of protein synthesis [11,12,13,14,15]. It has been shown that T2 administration to rats increases their resting metabolic rate by modulating mitochondrial function [16,17,18], prevents diet-induced obesity by enhancing burning of fats [19], and reduces liver steatosis in rats fed on a high-fat diet [20].…”
Section: Introductionmentioning
confidence: 99%
“…It stimulates the mitochondrial oxidative capacity and respiration rate [9,11,14,15,23] and increases FoF1-ATP synthase expression and activity in rat liver mitochondria [14,24]. …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that iodothyronines other than T 3 and T 4 can play a physiological role. Several evidences indicated that 3,5-diiodo-L-thyronine (T 2 ), previously considered as simple degradation product of T 3 , appears to influence energy metabolism [1], [14], [15]. T 2 is able to stimulate the mitochondrial oxidative capacity and respiration rate in mammals [1], [11], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Animal cells generate most of their ATP by oxidative phosphorylation (OXPHOS), a process located in the inner mitochondrial membrane. We have recently shown that the acute T 2 administration to hypothyroid rats increases F o F 1 -ATP synthase activity in liver mitochondria [15]. T 2 effects on different metabolic pathways have been shown to be more rapid than those of T 3 and often independent of protein synthesis [15][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation